Coronavirus disease 2019 and the kidney - Ravi Jangamani; Chakravarthy Thirumal; Sankaran Sundar (Wolters Kluwer Medknow Publications, 2020)
Coronavirus disease 2019 (COVID-19) is a highly contagious infection caused by severe acute respiratory syndrome coronavirus-2, primarily manifesting as acute respiratory illness but can affect multiple organs. The COVID-19 individuals have varied renal manifestations which includes acute kidney injury, proteinuria, and hematuria. The involvement of kidneys indicates the severity of illness and is one of the determinants of mortality. The individuals with chronic kidney diseases (CKD), on dialysis and with kidney transplantation are at higher risk of severe COVID-19 infection due to the poor immune response and a high prevalence of comorbidities. Here, we review the effects of COVID-19 on kidneys and its management in CKD, dialysis, and kidney transplantation individuals.